A methylation study implicates the rewiring of brain neural circuits during puberty in the emergence of sex differences in depression symptoms. (19th September 2021) - Chan, Robin F.; Copeland, William E.; Zhao, Min; Xie, Lin Y.; Costello, Jane; Aberg, Karolina A.; van den Oord, Edwin J.C.G.
Abstract : Background: Women are 1.5–3 times more likely to suffer from depression than men. This sex bias first emerges during puberty and then persists across the reproductive years. As the cause remains largely elusive, we performed a methylation‐wide association study (MWAS) to generate novel hypotheses. Methods: We assayed nearly all 28 million possible methylation sites in blood in 595 blood samples from 487 participants aged 9–17. MWASs were performed to identify methylation sites associated with increasing sex differences in depression symptoms as a function of pubertal stage. Epigenetic deconvolution was applied to perform analyses on a cell‐type specific level. Results: In monocytes, a substantial number of significant associations were detected after controlling the FDR at 0.05. These results could not be explained by plasma testosterone/estradiol or current/lifetime trauma. Our top results in monocytes were significantly enriched (ratio of 2.48) for genes in the top of a large genome‐wide association study (GWAS) meta‐analysis of depression and neurodevelopment‐related Gene Ontology (GO) terms that remained significant after correcting for multiple testing. Focusing on our most robust findings (70 genes overlapping with the GWAS meta‐analysis and the significant GO terms), we find genes coding for members of each of the major classes of axon guidance molecules (netrins, slits, semaphorins, ephrins, and cell adhesion molecules). Many of these genes were previously implicated in rodent studies of brain development and depression‐like phenotypes, as well as human methylation, gene expression and GWAS studies. Conclusions: Our study suggests that the emergence of sex differences in depression may be related to the differential rewiring of brain circuits between boys and girls during puberty.